Analisis Ekspor Impor Kelapa Sawit Indonesia Dalam Meningkatkan Pertumbuhan Ekonomi - Asraaf Efendi Batubara; Muhammad Faishal Yahya; Sultan Rasy Nasyaa; Purnama Ramadani Silalahi (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
Send out is the lawful development of products, items and administrations starting with one country then onto the next, as a rule as a feature of exchange. The term "export process" refers to the process by which goods or commodities are taken out of one country and brought into another country according to regulations established by the government. Numerous researchers have looked into how the economy is affected by imports and exports for more than a quarter of a century. This study was started by Balassa (1978), Kavoussi (1984), Ram (1985), and Moschos (1989), who looked into how imports and exports affected economic growth. The author employed a subjective strategy by utilizing literature studies, particularly methods for gathering information by comprehending and focusing on speculation from various related writings. Obviously Indonesia's development is profoundly subject to palm oil imports and products.